Foreign direct investment, trade openness and economic growth in BRICS countries: evidences from panel data. Issue 2 (3rd April 2021) - Banday, Umer Jeelanie; Murugan, Saravanan; Maryam, Javeria
Abstract: In this paper we investigate the causal relationship between foreign direct investment, trade openness and gross domestic product in BRICS countries over the period of 1990–2018. We applied auto regressive distributed lag model to test cointegration and the Dumitrescu and Hurlin Granger causality tests. Empirical results show that FDI and trade openness have a positive impact on long-term economic growth. We also find there is a long-run relationship from both real effective exchange rate and gross capital formation to economic growth. The main results of causality analysis reveal that there is bidirectional causality from foreign direct investment to economic growth, trade openness to foreign direct investment, and unidirectional causality from trade openness to foreign direct investment.